Functional characterization of peroxisomes and pathological consequences of peroxisomal dysfunction in the lung - Karnati, Srikanth; Justus Liebig University Giessen (My University, 2009)
Only sparse information is available from the literature on the molecular consequences and pathological alterations of the peroxisomal compartment and its enzyme composition in mouse and human lungs. Neither were any studies performed on the molecular consequences of peroxisome deficiency on the lung in knockout mouse models nor on the alterations of the peroxisomal compartment in human lung diseases. Therefore, in this dissertation the peroxisomal compartment and its related gene expression were characterized in different cell types of mouse (C57Bl/6J) and human lungs, using a variety of light-, fluorescence- and electron microscopic as well as biochemical and molecular biological techniques. Furthermore, the molecular consequences and pathological alterations in the lung of PEX11beta knockout mice with deficient peroxisome proliferation were characterized and the changes of the peroxisomal compartment in epithelial cells in the lung of IPF patients described. In contrast to the literature, the results obtained in this dissertation reveal for the first time the presence of peroxisomes in all distinct cell types in the lung and describe significant differences in their cell type-specific numerical abundance, structure and enzyme composition. In this respect, Pex14p proved to be the marker of choice for identification of the whole peroxisomal population, independent of the specific cell type. In contrast, catalase, an enzyme used in many morphological studies to identify these organelles, was only present in high amounts in AECII and Clara cells. Furthermore, peroxisomes of the alveolar and bronchiolar epithelium, as well as alveolar macrophages were rich in the lipid transporter ABCD3 and beta-oxidation enzymes, suggesting their involvement in the modification and recycling of surfactant lipids and in the control of pro-inflammatory lipid mediators and ligands for nuclear receptors of the PPAR family. Prior to this dissertation, no information was available on the peroxisomal compartment during the transdifferentiation process of alveolar epithelial cells (AECII to AECI) and the effect of KGF on peroxisomal markers in this process. The results in this dissertation revealed that some peroxisomal proteins and corresponding mRNAs were tremendously downregulated during AECII transition in the absence of KGF, whereas KGF application conserved the AECII phenotype and led to an increase of catalase and ether lipid synthesizing enzymes. These results correspond to the significant differences observed in the peroxisomal compartment between AECII and AECI in situ in lung sections. The results suggest that KGF might influence differentiation pathways in AECII, regulating peroxisome abundance and corresponding gene transcription. Additional results show that the peroxisomal numerical abundance is extremely high in AECII at birth, suggestive for a pivotal role of peroxisomal lipid metabolism during this period. Thereafter, with the concomitant increase of AECI number during alveolarization, the peroxisomal compartment is downregulated and is only prominent in AECII and alveolar macrophages in the mature adult lung.Furthermore, the molecular consequences of peroxisomal deficiency for regular lung structure and function were analyzed by the use of a knockout mouse model with a peroxisomal biogenesis defect, in which peroxisomal proliferation is disrupted (PEX11beta-/-). These mice showed severe alterations in the abundance of ROS metabolizing enzymes and significant differences in cell type-specific markers, involved in different maturation or signal transduction pathways in the lung. With the help of PEX11beta-/- mice, we could demonstrate that peroxisome deficiency influences lung morphogenesis and maturation, as indicated by severe alterations of the alveolarization process and the differences in the expression levels of mRNAs for components of signal transduction pathways, involved in distal morphogenesis (Wnt5a) and differentiation of individual lung cell types (PPARs). The severe alterations of antioxidant enzymes and pro-inflammatory proteins in PEX11beta-/- lungs are suggestive for disturbed antioxidant and pro-inflammatory response in PEX11beta-/- animals and suggest an essential role for peroxisomal metabolism in maintaining regular airway homeostasis.Finally, preliminary results reveal alterations of the peroxisomal compartment in the lung tissue of patients with idiopathic pulmonary fibrosis (IPF), a devastating human lung disease. The exact role and the molecular consequences of these peroxisomal alterations in IPF, however, have to be investigated in future studies. Taken together, the results of this dissertation suggest an important role of peroxisomes for regular lung development and adult lung homeostasis functions and indicate that this intracellular organelle compartment might be influenced as well in human lung diseases.

Zu Beginn dieser Dissertation waren kaum Informationen zu Peroxisomen in der Lunge und deren Enzymzusammensetzung in der Literatur vorhanden. Weiterhin waren keinerlei Studien mit Knockoutmausmodellen zu den molekularen Auswirkungen einer Peroxisomedefizienz in der Lunge oder zu Veränderungen des peroxisomalen Kompartiments bei Lungenerkrankungen des Menschen ausgeführt worden. Deshalb wurden in dieser Dissertation das peroxisomale Kompartiment und die Expression dessen zugehöriger Gene in verschiedenen Zelltypen der Mauslunge (C57Bl/6J) und der humanen Lunge mit unterschiedlichen Licht-, Fluoreszenz- und elektronenmikroskopischen Techniken, sowie biochemischen und molekularbiologischen Methoden charakterisiert. Weiterhin wurden die durch Peroxisomenproliferationsdefekt ausgelösten pathologischen Veränderungen im Lungengewebe bei PEX11beta-/- Knockoutmäusen charakterisiert und erste Veränderungen des peroxisomalen Kompartiments bei Patienten mit IPF beschrieben.Im Gegensatz zu früheren Arbeiten zeigen die Resultate dieser Dissertation zum ersten Mal, dass Peroxisomen in allen verschiedenen Zell-typen der Lunge vorkommen und beschreiben eindeutige Unterschiede in der zelltypspezifischen Organellenanzahl, deren Struktur und Enzymzusammensetzung. In diesem Zusammenhang erwies sich Pex14p als bester Marker zum Nachweis aller Peroxisomen, unabhängig des entsprechenden Zelltyps. Im Gegensatz hierzu war Katalase, ein Enzym, dass in den meisten Publikationen als Standard-Marker für Peroxisomen eingesetzt wird, nur in hoher Menge in AECII- und Clara-Zellen vorhanden. Weiterhin waren Peroxisomen des Alveolar- und Bronchialepithels und der Alveolarmakrophagen reich an ABCD3-Lipidtransporter und beta-Oxidationsenzymen, was ihre Funktion in der Modifizierung und Wiederverwertung des Lipidanteils von Surfactant und in der Kontrolle von pro-inflammatorischen Lipidmediatoren und Liganden für nukleäre Rezeptoren der PPAR Familie nahe legt. Zusätzlich Resultate erbrachten, dass die Peroxisomendichte und deren Enzymgehalt bereits bei der Geburt extrem hoch war, was eine wichtige Rolle des peroxisomalen Lipidstoffwechsels in der Lunge gerade in der perinatalen Periode vermuten lässt. Während der postnatalen Lungenentwicklung, mit gleichzeitiger Vermehrung von AECI in Rahmen des Alveolarisierungsprozesses wurde das peroxisomale Kompartiment herunterreguliert und blieb nur in AECII und Makrophagen der Alveolarregion der maturen adulten Lunge in starker Ausprägung vorhanden. Weiterhin zeigten die Resultate dieser Dissertation aus Zellkulturversuchen mit AECII, dass das peroxisomale Kompartiment und entsprechende mRNAs während der AECII-AECI-Umdifferenzierung drastisch herunterreguliert wird, während die Zugabe von KGF ins Kulturmedium den AECII-Phänotyp der Zellen erhält und sogar eine Induktion von Katalase und den peroxisomalen Enzymen der Etherlipidsynthese bewirkt. Diese Resultate spiegeln exakt die starken Unterschiede in der Ausprägung des peroxisomalen Kompartiments zwischen AECII und AECI in licht- und elektronmikroskopischen Präparaten des adulten Lungengewebes wider und legen nahe, dass KGF Differenzierungs signalwege des peroxisomalen Kompartiments in AECII beeinflusst, die die Ausprägung und die Transkription zugehöriger Gene induzieren. Weiterhin wurden in dieser Dissertation die molekularen Auswirkungen einer Peroxisomendefizienz auf die Lungenentwicklung in einem Knockoutmausmodell mit peroxisomalem Biogenesedefekt untersucht, durch den die Proliferation der Peroxisomen gestört ist (PEX11beta-/-). Knockoutmäuse mit PEX11beta-Defekt zeigten schwere Veränderungen des pulmonalen ROS- und Lipidstoffwechsels und wiesen eindeutige Unterschiede in der Expression zelltypspezifischer Marker auf. Mit Hilfe der PEX11beta-/- Mäuse konnte gezeigt werden, dass der Verlust peroxisomaler Funktionen zu Veränderungen der Alveolarisierung und der Expression von Wnt5a- oder PPAR-mRNAs führt, beides Faktoren, die in die distale Morphogenese (Wnt5a) oder die Ausdifferenzierung von Epithelzellen (PPARs) eingeschaltet sind. Schließlich konnten erste Resultate zu Veränderungen der Peroxisomen und deren Enzymzusammensetzung in Lungengewebe von Patienten mit idiopathischer Lungenfibrose (IPF), einer tödlichen Lungenerkrankung, erhoben werden. Die genaue Rolle der Veränderungen des peroxisomalen Stoffwechsels in der Lunge von IPF-Patienten muss jedoch in zukünftige Studien aufgeklärt werden.Zusammenfassend legen die Resultate der Dissertation nahe, dass das peroxisomale Kompartiment und dessen Stoffwechselfunktionen eine wichtige Rolle in der Ausdifferenzierung bei der Lungenentwicklung spielen und für die reguläre Funktion und den Homöostaseerhalt im adulten Lungengewebe notwendig sind, sowie bei Lungenerkrankungen verändert werden können.
Keywords: ddc:610